2010
DOI: 10.1111/j.1365-2435.2009.01647.x
|View full text |Cite
|
Sign up to set email alerts
|

Support from the underground: Induced plant resistance depends on arbuscular mycorrhizal fungi

Abstract: Summary1. Mycorrhizal symbiosis is thought to affect interactions between plants and herbivores by its influence on plant growth, nutrition and the plants defence system. Moreover, arbuscular mycorrhizal fungi (AMF) may enhance the inducibility of resistance responses. Until now, induction of plant resistance has not been considered to be a mechanism affecting the outcome of mycorrhization for plant-herbivore interactions. 2. Here, we test the hypothesis that the resistance of plants against herbivores depends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 64 publications
3
82
2
Order By: Relevance
“…Recently, Kempel et al (2010) confirmed earlier work that mycorrhizal colonization increased plant and aboveground herbivore (caterpillar) performance; but after inducing resistance due to short-term herbivory, the beneficial effect of mycorrhizal colonization on plant and herbivore performance disappeared. The authors concluded that plant defence against herbivory depends on AMF due to the allocation of resources into defence compounds, and pointed to the relevance of AMF-induced plant resistance.…”
Section: Mycorrhizal Fungisupporting
confidence: 64%
“…Recently, Kempel et al (2010) confirmed earlier work that mycorrhizal colonization increased plant and aboveground herbivore (caterpillar) performance; but after inducing resistance due to short-term herbivory, the beneficial effect of mycorrhizal colonization on plant and herbivore performance disappeared. The authors concluded that plant defence against herbivory depends on AMF due to the allocation of resources into defence compounds, and pointed to the relevance of AMF-induced plant resistance.…”
Section: Mycorrhizal Fungisupporting
confidence: 64%
“…Since soil communities include pathogens, parasites, and herbivores as well as beneficial groups ( e.g . mycorrhizae, rhizobia) [14], [15], the overall impact of soil biota on plant performance will reflect the net effect of both negative and positive interactions [16]. Strong negative impacts of soil microbial communities on invasive plants have mostly been observed in natural population of these plants growing in their native ranges [11], [17] indicating that negative interactions are relatively stronger than beneficial ones [16].…”
Section: Introductionmentioning
confidence: 99%
“…There is accumulating knowledge suggesting AMF as a critical factor for plant resistance to aboveground herbivory (Koricheva et al, 2009;Kempel et al, 2010). Priming of jasmonate-regulated defense mechanisms of plants could be an explanation for mycorrhiza-induced resistance (Pozo and AzconAguilar, 2007;Kempel et al, 2010). Indirect defenses of plants against aboveground herbivores may also be induced by AMF through altering volatile profiles to attract parasitoids (Guerrieri et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…This could be due to changes in plant defensive chemicals induced by AMF root colonization (Koricheva et al, 2009). There is accumulating knowledge suggesting AMF as a critical factor for plant resistance to aboveground herbivory (Koricheva et al, 2009;Kempel et al, 2010). Priming of jasmonate-regulated defense mechanisms of plants could be an explanation for mycorrhiza-induced resistance (Pozo and AzconAguilar, 2007;Kempel et al, 2010).…”
Section: Discussionmentioning
confidence: 98%